Preparation method of multifunctional composite proton exchange membrane
The multifunctional composite proton exchange membrane prepared by electrospinning technology solves the problems of uneven and instability of proton conduction through the synergistic modification method and nanofillers, significantly improving the proton conductivity and mechanical properties, and is suitable for high-performance fuel cells.
Patent Information
- Application Number
- CN202411722849.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing proton exchange membranes have defects in uneven proton conduction and instability under various conditions, making it difficult to meet the requirements of high-performance fuel cells for isotropy of proton exchange membranes.
The multifunctional composite proton exchange membrane is prepared by electrospinning technology, and modified by blending and modification method, including sulfonated polymer materials, configuration of cast film liquid, electrospinning, heat treatment and post-treatment, and the microstructure and performance of the membrane are optimized using the synergistic action of nanofillers and tackifiers.
It significantly improves the proton conductivity by 50-100%, strengthens the mechanical properties by 20-50%, maintains the uniformity and stability of proton conduction, and improves the overall performance and reliability of fuel cells.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a multifunctional composite proton exchange membrane, belonging to the technical field of proton exchange membranes. The proton exchange membrane has the advantages of high proton conductivity, good chemical stability, excellent mechanical properties, etc., and is suitable for fuel cells and other fields. Background Art
[0002] As the global demand for clean energy grows, fuel cells have attracted widespread attention as an efficient and environmentally friendly energy conversion device. In fuel cells, proton exchange membranes are one of the core components, and their performance directly affects key performance indicators such as fuel cell output power, efficiency, life and reliability. At present, the phase inversion method is a commonly used method for preparing proton exchange membranes. However, the prepared membranes have problems such as uneven pore size distribution, difficulty in accurately controlling membrane thickness, and poor mechanical properties. These defects lead to uneven proton conduction, reduce the performance stability of fuel cells, and are susceptible to mechanical stress and chemical corrosion during long-term use, resulting in rupture or performance degradation, making it difficult to meet the isotropic requirements of proton exchange membranes for high-performance fuel cells.
[0003] Electrospinning technology has the characteristics of preparing fibers with diameters ranging from tens of nanometers to several microns. This nanoscale fiber structure has extremely high specific surface area and porosity. High specific surface area helps to increase the loading of proton exchange groups and provide more active sites to promote proton conduction; while high porosity provides abundant transmission channels for protons, significantly improving proton conductivity. In addition, electrospinning technology can accurately control the thickness of the membrane, reduce the resistance of the membrane, and improve the performance of fuel cells. The fibers are uniformly deposited during the electrospinning process to ensure the uniformity of the thickness of the membrane and the consistency of the performance of the membrane in various regions.
[0004] In the field of proton exchange membranes, polyethersulfone has been used in medium and low temperature fuel cells, but it has the problem of low proton conductivity. Due to the lack of effective proton conduction channels and groups in the chemical structure, it is easy to absorb water and swell under high humidity and high temperature, affecting performance and life. At present, there are patents that use electrospinning technology to prepare polyethersulfone proton exchange membranes. Through the synergistic effect of aminosulfonic acid, hydroxyethyl cellulose and sulfonated polyethersulfone, the mechanical properties, proton conductivity, water absorption and hydrolysis stability are improved. However, there is no literature reporting on the relevant technology of preparing proton exchange membranes using the synergistic effect between nanoparticles, thickeners and sulfonated polyethersulfone.
[0005] In the patent with publication number CN115210160A, a high-temperature and high-proton conductivity proton exchange membrane was prepared. Under the conditions of 120 °C and 50% relative humidity, the proton conductivity reached more than 0.02 s / cm; in the patent with publication number CN117799260A, the proton conductivity of the prepared proton exchange membrane in a high-temperature and low-humidity environment was effectively improved, but the specific conductivity data was not clearly given. The patent with publication number CN118943404A mentioned that the ultra-thin proton exchange membrane for fuel cells prepared by it for unmanned aerial vehicles has high mechanical strength, but the specific strength value is not clear; in the patent with authorization announcement number CN115948012B of Huadian Heavy Industry Co., Ltd., the thickness of the fiber-reinforced proton exchange membrane for hydrogen production by electrolysis of water is 50-100μm, and it has good dimensional stability and mechanical strength. However, there is no public patent to solve the defects of proton exchange membrane in uneven proton conduction and instability under various conditions. Therefore, it is of great significance to prepare multifunctional composite proton exchange membranes using new processes. Summary of the invention
[0006] The present invention relates to a method for preparing a multifunctional composite proton exchange membrane, aiming to overcome the difficulty of preparing proton exchange membranes by phase inversion method in meeting the isotropy requirements of high-performance fuel cells and improve the proton conductivity, chemical stability, mechanical properties, etc. of the proton exchange membrane.
[0007] The multifunctional proton exchange membrane prepared by electrospinning in the present invention is first modified by a blending modification method, comprising the following steps: Step 1): Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are composed of the following mass percentages: 10-14% PES particles are added to 60-80 mL concentrated sulfuric acid, heated to 40°C, stirred for reaction for 24 hours, then filtered, washed and dried to obtain sulfonated PES material.
[0008] Step 2): Preparation of casting solution: The casting solution is prepared by the following components in mass percentage: 12-14% of the sulfonated polyethersulfone material prepared in step 1), 1-1.5% of the nanofiller, 6-8% of the thickener, and the rest is the solvent. Dissolve the sulfonated polyethersulfone in the solvent, then add the modified nanofiller and the thickener, heat and stir until completely dissolved, and let the dissolved sPES solution stand until the bubbles disappear in the solution, and then set aside.
[0009] Step 3): Electrospinning: Inject the spinning solution into a 10 mL syringe, fix the syringe on the electrospinning device, connect the spinneret to the anode of the electrostatic generator, connect the collecting device to the ground and the cathode of the electrostatic generator, control the spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate, and use tin foil as the receiving material.
[0010] Step 4): Heat treatment: The proton exchange membrane obtained by electrospinning is dried at room temperature, then placed in a 95-100°C vacuum oven for heat treatment for 3-4 h, and then hot pressed for 10-15 min at 100-120°C and 0.1 MPa using a hot press to improve the mechanical properties and proton conductivity of the membrane.
[0011] Step 5): Post-processing: cutting, cleaning and other post-processing are performed on the proton exchange membrane after heat treatment to obtain the final polyethersulfone proton exchange membrane product.
[0012] Preferably, the nanofiller in step 2) is mainly one of TiO2, ZrO2, SiO2 and graphene.
[0013] Preferably, the viscosity enhancer in step 2) is one of thermoplastic polyurethane, cellulose nanofiber and polyvinyl alcohol.
[0014] Preferably, the solvent in step 2) is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide or a mixed solution thereof.
[0015] Preferably, in step 2), the electrospinning voltage is 14-16 kV.
[0016] Preferably, in step 2), the distance from the spinneret to the receiving plate is 10-15 cm Preferably, the spinning solution flow rate in step 2) is 1.2-1.5 mL / h The polyethersulfone proton exchange membrane prepared by the electrostatic spinning technology of the present invention has the following preparation principle: the introduction of sulfonic acid groups can promote the transfer of protons, improve the proton conductivity of fuel cells, thereby improving the performance and efficiency of fuel cells, and at the same time has good chemical stability and thermal stability, can maintain good performance under the working conditions of fuel cells, and help improve the reliability and durability of fuel cells. The nanoscale fiber structure formed by the electrostatic spinning technology has extremely high specific surface area and porosity, provides more active sites and abundant transmission channels for proton conduction, and significantly improves the proton conductivity. Fine regulation of the membrane microstructure can be achieved by adjusting the parameters in the electrostatic spinning process. The incorporation of nanofillers can interact with polyethersulfone to form a continuous proton transmission network, thereby increasing the transmission path and transmission efficiency of protons. The nanofillers themselves have high thermal stability, and their addition can also increase the thermal decomposition temperature of the polyethersulfone proton exchange membrane, so that it can still maintain good performance at higher temperatures. Under high temperature conditions, the nanofillers can also inhibit the thermal shrinkage of the polyethersulfone membrane, maintain the size and structural stability of the membrane, and ensure the continuity of proton transmission.
[0017] Electrochemical impedance spectroscopy (EIS) measures the AC impedance on both sides of the proton exchange membrane at different frequencies to obtain an impedance spectrum. The proton conduction performance is evaluated based on the resistance information in the impedance spectrum. Uneven proton conduction will result in different resistances at different locations, which will be reflected in the impedance spectrum.
[0018] The proton exchange membrane was immersed in solutions with different pH values to simulate acidic and alkaline environments. After 12 hours of immersion, the appearance of the proton exchange membrane was observed, and the weight loss and proton conductivity were measured. The improvement effect of its chemical stability was comprehensively evaluated.
[0019] The proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the ion exchange capacity IEC value can reach 1.0-2.0 meq / g, the swelling degree is 28-40%, and the tensile strength can reach 35-57 MPa. The mechanical properties of the membrane are significantly improved. The EIS evaluation results show that the proton conduction of the membrane is uniform, the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration, the weight loss is less than 5%, and the decrease in proton conductivity does not exceed 30% of the initial conductivity. Beneficial Effects
[0020] The method of preparing a multifunctional polyethersulfone proton exchange membrane by electrospinning has many beneficial effects. In terms of proton exchange membrane performance, the proton conductivity is significantly improved by 50-100%, the nanofiber network structure optimizes the proton conduction path, the mechanical properties are enhanced by 20-50%, and the uniformity and stability of proton conduction are maintained. For fuel cell systems, the overall performance is improved and the scope of application is expanded. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the dense surface of the polyethersulfone modified proton exchange membrane of Example 2 of the present invention Figure 2-1 This is the modified polyethersulfone casting solution of Example 4 of the present invention. Figure 2-2 This is a picture of the polyethersulfone modified proton exchange membrane of Example 4 of the present invention Table 1 Proton conductivity, IEC value, swelling degree, tensile strength, weight loss, and proton conductivity decrease of the proton exchange membranes prepared in Examples 1-5 of the present invention. DETAILED DESCRIPTION
[0022] In order to understand the present invention more deeply and comprehensively, the following will describe and analyze the preparation method of the multifunctional composite proton exchange membrane of the present invention and its performance in detail through specific examples to demonstrate the feasibility and superiority of the present invention in practical applications: Example
[0023] Step 1): Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are composed of the following: 10 g of PES particles are added to 60 mL of concentrated sulfuric acid, heated to 40 ° C, stirred for reaction for 24 hours, and then filtered, washed and dried to obtain sulfonated PES material.
[0024] Step 2): Preparation of casting solution: The casting solution is prepared from the following components: 1.3 g sulfonated polyethersulfone, 0.1 g SiO2, 0.7 g thermoplastic polyurethane, 1.4 g N,N-dimethylformamide, and 6.5 g N,N-dimethylacetamide. Dissolve the sulfonated polyethersulfone in a DMF / DMAc mixed solvent, then add the modified nanofiller SiO2 and TPU, heat and stir until completely dissolved, and let the dissolved PES solution stand until the bubbles disappear in the solution, and then set aside.
[0025] Step 3): Electrospinning: Inject the spinning solution into a 10 mL syringe, fix the syringe on the electrospinning device, connect the spinneret to the anode of the electrostatic generator, connect the collecting device to the ground and the cathode of the electrostatic generator, control the spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate, and use tin foil as the receiving material. The electrospinning pressure is 16 kV, the distance from the spinneret to the receiving plate is 13 cm, and the spinning solution flow rate is 1.3 mL / h.
[0026] Step 4): Heat treatment: The proton exchange membrane obtained by electrospinning was dried at room temperature, then placed in a 95 °C vacuum oven for heat treatment for 3 h, and then hot pressed for 10 min at 100 °C and 0.1 MPa using a hot press to improve the mechanical properties and proton conductivity of the membrane.
[0027] Step 5): Post-processing: cutting, cleaning and other post-processing are performed on the proton exchange membrane after heat treatment to obtain the final polyethersulfone proton exchange membrane product.
[0028] The polyethersulfone proton exchange membrane prepared by the electrospinning technology of the present invention is characterized in that the proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the IEC value can reach 2.0 meq / g, the swelling degree is 30%, and the tensile strength can reach 57 MPa. The mechanical properties of the membrane are significantly improved, and the EIS method evaluation results show that the proton conduction of the membrane is uniform, the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration, the weight loss is less than 5%, and the proton conductivity decreases by 24% of the initial conductivity. Example
[0029] Step 1): Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are as follows: 15 g of PES particles are added to 80 mL of concentrated sulfuric acid, heated to 40 ° C, stirred for reaction for 24 hours, and then filtered, washed and dried to obtain sulfonated PES material.
[0030] Step 2): Preparation of casting solution: The casting solution is prepared from the following components: 1.4 g sulfonated polyethersulfone, 0.1 g TiO2, 0.6 g thermoplastic polyurethane, 1.4 g N,N-dimethylformamide, and 6.5 g N,N-dimethylacetamide. Dissolve the sulfonated polyethersulfone in a DMF / DMAc mixed solvent, then add the modified nanofiller TiO2 and the thickener TPU, heat and stir until completely dissolved, and let the dissolved PES solution stand until the bubbles disappear in the solution, and then set aside.
[0031] Step 3): Electrospinning: Inject the spinning solution into a 10 mL syringe, fix the syringe on the electrospinning device, connect the spinneret to the anode of the electrostatic generator, connect the collecting device to the ground and the cathode of the electrostatic generator, control the spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate, and use tin foil as the receiving material. The electrospinning pressure is 15 kV, the distance from the spinneret to the receiving plate is 15 cm, and the spinning solution flow rate is 1.5 mL / h.
[0032] Step 4): Heat treatment: The proton exchange membrane obtained by electrospinning was dried at room temperature, then placed in a 100 °C vacuum oven for heat treatment for 4 h, and then hot pressed for 15 min at 120 °C and 0.1 MPa using a hot press to improve the mechanical properties and proton conductivity of the membrane.
[0033] Step 5): Post-processing: cutting, cleaning and other post-processing are performed on the proton exchange membrane after heat treatment to obtain the final polyethersulfone proton exchange membrane product.
[0034] The polyethersulfone proton exchange membrane prepared by the electrospinning technology of the present invention is characterized in that the proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the IEC value can reach 1.4 meq / g, the swelling degree is 28%, and the tensile strength can reach 40 MPa. The mechanical properties of the membrane are significantly improved. The EIS method evaluation results show that the proton conduction of the membrane is uniform, and the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration. The weight loss is less than 5%, and the proton conductivity decreases by 27% of the initial conductivity. The dense surface scanning electron microscope image of the membrane is as follows Figure 1 shown. Example
[0035] Step 1): Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are as follows: 10 g of PES particles are added to 70 mL of concentrated sulfuric acid, heated to 40 ° C, stirred for reaction for 24 hours, and then filtered, washed and dried to obtain sulfonated PES material.
[0036] Step 2): Preparation of casting solution: The casting solution is prepared from the following components: 1.2 g sulfonated polyethersulfone, 0.15 g graphene, 0.7 g polyvinyl alcohol, and 7.95 g dimethyl sulfoxide. Dissolve the sulfonated polyethersulfone in dimethyl sulfoxide solvent, then add the modified nanofiller graphene and polyvinyl alcohol, heat and stir until completely dissolved, and let the dissolved sPES solution stand until the bubbles disappear in the solution, and then set aside.
[0037] Step 3): Electrospinning: Inject the spinning solution into a 10 mL syringe, fix the syringe on the electrospinning device, connect the spinneret to the anode of the electrostatic generator, connect the collecting device to the ground and the cathode of the electrostatic generator, control the spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate, and use tin foil as the receiving material. The electrospinning pressure is 14 kV, the distance from the spinneret to the receiving plate is 10 cm, and the spinning solution flow rate is 1.2 mL / h.
[0038] Step 4): Heat treatment: The proton exchange membrane obtained by electrospinning was dried at room temperature, then placed in a 95-100°C vacuum oven for heat treatment for 3-4 h, and then hot pressed for 10 min at 110°C and 0.1 MPa using a hot press to improve the mechanical properties and proton conductivity of the membrane.
[0039] Step 5): Post-processing: cutting, cleaning and other post-processing are performed on the proton exchange membrane after heat treatment to obtain the final polyethersulfone proton exchange membrane product.
[0040] The polyethersulfone proton exchange membrane prepared by the electrospinning technology of the present invention is characterized in that the proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the IEC value can reach 1.0 meq / g, the swelling degree is 40%, and the tensile strength can reach 35 MPa. The mechanical properties of the membrane are significantly improved, and the EIS method evaluation results show that the proton conduction of the membrane is uniform, the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration, the weight loss is less than 5%, and the decrease in proton conductivity is 30% of the initial conductivity. Example
[0041] Step 1): Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are composed of the following: 10 g of PES particles are added to 60 mL of concentrated sulfuric acid, heated to 40 ° C, stirred for reaction for 24 hours, and then filtered, washed and dried to obtain sulfonated PES material.
[0042] Step 2): Preparation of casting solution: The casting solution is prepared from the following components: 1.4 g sulfonated polyethersulfone, 0.12 g TiO2, 0.78 g cellulose nanofibers, 0.9 g N,N-dimethylformamide, and 6.8 g N,N-dimethylacetamide. Dissolve the sulfonated polyethersulfone in DMF / DMAc solvent, then add the modified nanofiller TiO2 and cellulose nanofibers, heat and stir until completely dissolved, and let the dissolved sPES solution stand until the bubbles disappear in the solution, and then set aside.
[0043] Step 3): Electrospinning: Inject the spinning solution into a 10 mL syringe, fix the syringe on the electrospinning device, connect the spinneret to the anode of the electrostatic generator, connect the collecting device to the ground and the cathode of the electrostatic generator, control the spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate, and use tin foil as the receiving material. The electrospinning pressure is 16 kV, the distance from the spinneret to the receiving plate is 13 cm, and the spinning solution flow rate is 1.4 mL / h.
[0044] Step 4): Heat treatment: The proton exchange membrane obtained by electrospinning was dried at room temperature, then placed in a 100 °C vacuum oven for heat treatment for 3.5 h, and then hot pressed for 15 min at 110 °C and 0.1 MPa using a hot press to improve the mechanical properties and proton conductivity of the membrane.
[0045] Step 5): Post-processing: cutting, cleaning and other post-processing are performed on the proton exchange membrane after heat treatment to obtain the final polyethersulfone proton exchange membrane product.
[0046] The polyethersulfone proton exchange membrane prepared by the electrospinning technology of the present invention is characterized in that the proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the IEC value can reach 1.7 meq / g, the swelling degree is 32%, and the tensile strength can reach 48 MPa. The mechanical properties of the membrane are significantly improved. The EIS method evaluation results show that the proton conduction of the membrane is uniform, and the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration. The weight loss is less than 5%, and the proton conductivity decreases by 28% of the initial conductivity. The casting liquid is as follows Figure 2-1 As shown, the proton exchange membrane Figure 2-2 shown. Example
[0047] Step 1): Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are composed of the following: 10 g of PES particles are added to 60 mL of concentrated sulfuric acid, heated to 40 ° C, stirred for reaction for 24 hours, and then filtered, washed and dried to obtain sulfonated PES material.
[0048] Step 2): Preparation of casting solution: The casting solution is prepared from the following components: 1.2 g sulfonated polyethersulfone, 0.15 g ZrO2, 0.75 g polyvinyl alcohol, and 7.9 g N,N-dimethylformamide. Dissolve the sulfonated polyethersulfone in N,N-dimethylformamide solvent, then add the modified nanofiller ZrO2 and the thickener polyvinyl alcohol, heat and stir until completely dissolved, and let the dissolved sPES solution stand until the bubbles disappear in the solution, and then set aside.
[0049] Step 3): Electrospinning: Inject the spinning solution into a 10 mL syringe, fix the syringe on the electrospinning device, connect the spinneret to the anode of the electrostatic generator, connect the collecting device to the ground and the cathode of the electrostatic generator, control the spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate, and use tin foil as the receiving material. The electrospinning pressure is 16 kV, the distance from the spinneret to the receiving plate is 12 cm, and the spinning solution flow rate is 1.3 mL / h.
[0050] Step 4): Heat treatment: The proton exchange membrane obtained by electrospinning was dried at room temperature, then placed in a vacuum oven at 100°C for 4 h, and then hot pressed for 15 min at 110°C and 0.1 MPa using a hot press to improve the mechanical properties and proton conductivity of the membrane.
[0051] Step 5): Post-processing: cutting, cleaning and other post-processing are performed on the proton exchange membrane after heat treatment to obtain the final polyethersulfone proton exchange membrane product.
[0052] The polyethersulfone proton exchange membrane prepared by the electrospinning technology of the present invention is characterized in that the proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the IEC value can reach 1.5 meq / g, the swelling degree is 32%, and the tensile strength can reach 45 MPa. The mechanical properties of the membrane are significantly improved, and the EIS method evaluation results show that the proton conduction of the membrane is uniform, the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration, the weight loss is less than 5%, and the decrease in proton conductivity is 27% of the initial conductivity.
[0053] Table 1
Claims
1. A method for preparing a multifunctional composite proton exchange membrane, characterized in that: The following steps are involved: (1) Sulfonation of polymer materials: The substances involved in the sulfonation step of PES are composed of the following mass percentages: 10-14% PES particles are added to 60-80 mL concentrated sulfuric acid, heated to 40°C, stirred for reaction for 24 hours, and then filtered, washed, and dried to obtain sulfonated PES material; (2) Preparation of casting solution: The casting solution is prepared by the following components in percentage by mass: 12-15% of the sulfonated polyethersulfone material prepared in step (1), 1-1.5% of the nanofiller, 6-8% of the thickener, and the rest is the solvent. Dissolve the sulfonated polyethersulfone in a suitable solvent, then add the modified nanofiller and the thickener, heat and stir until completely dissolved, and let the dissolved sPES solution stand until the bubbles disappear in the solution, and then set aside; (3) Electrospinning: The spinning solution was injected into a 10 mL syringe, which was fixed on the electrospinning device. The spinneret was connected to the anode of the electrostatic generator. The collecting device was grounded and connected to the cathode of the electrostatic generator. The spinning voltage, the distance from the spinneret to the receiving plate, and the spinning solution flow rate were controlled. Tin foil was used as the receiving material. (4) Heat treatment: The proton exchange membrane obtained by electrospinning is dried at room temperature, then placed in a vacuum oven at 95-100 °C for 3-4 h, and then hot pressed in a hot press at 100-120 °C and 0.1 MPa for 10-15 min to improve the mechanical properties and proton conductivity of the membrane; (5) Post-processing: The proton exchange membrane after heat treatment is cut, cleaned and other post-processing is performed to obtain the final polyethersulfone proton exchange membrane product.
2. The multifunctional proton exchange membrane according to claim 1, characterized in that: The laboratory-prepared sulfonated polyethersulfone replaces the purchase of finished sulfonated polyethersulfone materials to accurately control the degree of sulfonation and thus ensure the proton conduction efficiency; the membrane material prepared by the electrospinning process has a specific microstructure, which is beneficial to improving the mechanical strength and proton conductivity of the proton exchange membrane; the special structure and high specific surface area of the incorporated nanofiller can provide more transmission channels and adsorption sites for protons.
3. The method for preparing a multifunctional composite proton exchange membrane according to claim 1, characterized in that: Nanofillers are mainly one of TiO2, ZrO2, SiO2, and graphene.
4. According to the preparation of the casting solution in claim 1: the viscosity enhancer is one of thermoplastic polyurethane, cellulose nanofiber and polyvinyl alcohol.
5. The preparation of the casting solution according to claim 1: the solvent is one of N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide or a mixed solution.
6. The method for preparing a multifunctional composite proton exchange membrane according to claim 1: the electrospinning voltage is 14-16 kV.
7. The method for preparing a multifunctional composite proton exchange membrane according to claim 1: the distance from the spinneret to the receiving plate is 10-15 cm.
8. The method for preparing a multifunctional composite proton exchange membrane according to claim 1: the spinning solution flow rate is 1.2-1.5 mL / h.
9. A method for preparing a multifunctional composite proton exchange membrane according to any one of claims 1 to 8, characterized in that: The proton conductivity of the proton exchange membrane is greater than 0.15 s / cm, the ion exchange capacity (IEC) value can reach 1.0-2.0 meq / g, the swelling degree is 28-40%, and the tensile strength can reach 35-57 MPa. The mechanical properties of the membrane are significantly improved. The EIS evaluation results show that the proton conduction of the membrane is uniform, and the appearance of the proton exchange membrane does not show obvious swelling, rupture or discoloration, the weight loss is less than 5%, and the decrease in proton conductivity does not exceed 30% of the initial conductivity.
Citation Information
Patent Citations
Storage assembly
CN115210160A
A fiber-reinforced proton exchange membrane for hydrogen production by water electrolysis and its preparation method
CN115948012B
Reinforcing layer for wide-temperature-range proton exchange membrane and manufacturing method of reinforcing layer
CN117799260A
Ultra-thin proton exchange membrane of fuel cell for unmanned aerial vehicle and preparation method of ultra-thin proton exchange membrane
CN118943404A